2015
DOI: 10.5498/wjp.v5.i1.68
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music and music therapy on mood in neurological patients

Abstract: Mood disorder and depressive syndromes represent a common comorbid condition in neurological disorders with a prevalence rate that ranges between 20% and 50% of patients with stroke, epilepsy, multiple sclerosis, and Parkinson's disease. Notwithstanding, these conditions are often under-diagnosed and under-treated in the clinical practice and negatively affect the functional recovery, the adherence to treatment, the quality of life, and even the mortality risk. In addition, a bidirectional association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(103 citation statements)
references
References 93 publications
4
80
0
13
Order By: Relevance
“…Improved attention and participation to the environmental stimuli in some children, not reported so far, to our knowledge, might be correlated with the beneficial effect of music therapy on mood [13] as well as on cognition [14] and with the well-known effect of activation of parasympathetic tone [15].…”
Section: Discussionmentioning
confidence: 52%
“…Improved attention and participation to the environmental stimuli in some children, not reported so far, to our knowledge, might be correlated with the beneficial effect of music therapy on mood [13] as well as on cognition [14] and with the well-known effect of activation of parasympathetic tone [15].…”
Section: Discussionmentioning
confidence: 52%
“…Clinical studies have also indicated an important result; that is, music could influence human emotions and treatment outcome in a positive way (Carlson et al, 2015;Iyendo, 2016). With the long history of its medical use, music therapy has been wildly applied to various physical, psychological, functional and educational settings to help improve the physiological and psychological status of patients (Bradt, Dileo, Magill, & Teague, 2016;Raglio et al, 2015;Silverman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Music decreases the anxiety and pain scores of patients during SWL and is associated with higher satisfaction scores for remedies (Akbas et al, 2016). Music engages a variety of brain areas involved in emotion, motivation, cognition, and motor skills, and musical input have been utilized to enhance socialization and cognitive, sentimental, and neuromotor operation (Raglio et al, 2015). Applied music, through its main elements -pitch, dynamics and harmony, meter, tempo and rhythm, allows the organization of movement in time and space, leads to movement fluency, provides impulses to muscles and supplies rhythmic instructions by which to initiate and maintain activity (Bukowska et al, 2016).…”
Section: Resultsmentioning
confidence: 99%